Imagining the impossible before breakfast: the relation between creativity, dissociation, and sleep - van Heugten - van der Kloet, Dalena; Cosgrave, Jan; Merckelbach, Harald; Haines, Ross; Golodetz, Stuart; Lynn, Steven Jay (Frontiers in Psychology, 2015)
Dissociative symptoms have been related to higher Rapid Eye Movement (REM) sleep density, a sleep phase during which hyperassociativity may occur. This may enhance artistic creativity during the day. To test this hypothesis, we conducted a creative photo contest to explore the relation between dissociation, sleep, and creativity. During the contest, participants (N=72) took one photo per day for five consecutive days, based on specific daily themes (consisting of single words) and the instruction to take as creative a photo as possible each day. Furthermore, they completed daily measures of state dissociation and a short sleep diary. The photos and their captions were ranked by two professional photographers and two clinical psychologists based on creativity, originality, bizarreness, and quality. We expected that dissociative people would rank higher in the contest compared with low-dissociative participants, and that the most original photos would be taken on days when the participants scored highest on acute dissociation. We found that acute dissociation predicted a higher ranking on creativity. Poorer sleep quality and fewer hours of sleep predicted more bizarreness in the photos and captions. None of the trait measures could predict creativity. In sum, acute dissociation related to enhanced creativity. These findings contribute to our understanding of dissociative symptomatology.